Práticas individuais e coletivas dos enfermeiros na atenção primária à saúde: um panorama da região norte do Brasil - VELOSO, Caroline de Morais Zanchin (Universidade Federal do Pará, 2025)
INTRODUCTION: territorial characteristics, with an emphasis on the geography of the North region, require individual and collective practices in the work of Primary Health Care nurses that meet the peculiarities of the populations that inhabit this territory. OBJECTIVE: to analyze individual and collective practices that are associated with the dificulties of nurses working in Primary Health Care in the North region. METHOD: mixed methods study carried out with Primary Health Care nurses in the North region, between November 2019 and August 2021, using an electronic form and interview. The data were analyzed using the Bioestat program and the IRaMuTeQ® software, using Bardin's thematic content analysis. RESULTS: 626 nurses participated in the quantitative stage and 31 in the qualitative stage. Difficulty in carrying out practices was described by 15.7% (98/626) of nurses. Four categories were identified in the qualitative analysis: professional autonomy in their activities; need for a prescription from another professional to complete a service; work facilities; difficulties at work. Among collective practices, there was an association between difficulty and participation in the management of inputs (p = 0.03), but it was evident from the interviews that the nurse participates in the request for technical material, but does not receive it as requested. In individual practices, there was an association between the difficulty in carrying out a consultation (p = 0.03) and the prescription of medications (p = 0.02). The qualitative analysis demonstrates that the nurse needs a prescription from another professional to complete a service he started. The association between difficulty and resolution showed significance between prenatal consultation (p = 0.000), activities to monitor child growth and development (p= 0.001; 25%) and family planning (p= 0.000; 25.7%) . However, these are practices that nurses report that they exercise with greater autonomy. The association of difficulty with caring for hypertensive patients (p <0.0001) and diabetics (p<0.0001) also showed insufficient resolution. In these activities, the nurse describes needing the doctor to prescribe medications and complete the care. CONCLUSION: The work carried out by primary health care nurses requires the continuous improvement of these professionals' skills and abilities, especially with regard to nursing consultations and medication prescriptions. The implementation of nursing protocols and continuing education help in the development of professional autonomy, aiming at the quality of the service and the resolution of the assistance provided to users.